Neoadjuvant antiangiogenic therapy reveals contrasts in primary and metastatic tumor efficacy. Issue 12 (31st October 2014) - Ebos, John ML; Mastri, Michalis; Lee, Christina R; Tracz, Amanda; Hudson, John M; Attwood, Kristopher; Cruz‐Munoz, William R; Jedeszko, Christopher; Burns, Peter; Kerbel, Robert S
Abstract Thousands of cancer patients are currently in clinical trials evaluating antiangiogenic therapy in the neoadjuvant setting, which is the treatment of localized primary tumors prior to surgical intervention. The rationale is that shrinking a tumor will improve surgical outcomes and minimize growth of occult micrometastatic disease—thus delaying post‐surgical recurrence and improving survival. But approved VEGF pathway inhibitors have not been tested in clinically relevant neoadjuvant models that compare pre‐ and post‐surgical treatment effects. Using mouse models of breast, kidney, and melanoma metastasis, we demonstrate that primary tumor responses to neoadjuvant VEGFR TKI treatment do not consistently correlate with improved post‐surgical survival, with survival worsened in certain settings. Similar negative effects did not extend to protein‐based VEGF pathway inhibitors and could be reversed with altered dose, surgical timing, and treatment duration, or when VEGFR TKIs are combined with metronomic 'anti‐metastatic' chemotherapy regimens. These studies represent the first attempt to recapitulate the complex clinical parameters of neoadjuvant therapy in mice and identify a novel tool to compare systemic antiangiogenic treatment effects on localized and disseminated disease.